Development of a Complex Intervention to Support the Use of Sedative Drugs in Specialist Palliative Care (iSedPall) - Kauzner, Saskia; Schneider, Manuela; Heckel, Maria; Klein, Carsten; Bausewein, Claudia; Schildmann, Eva; Bazata, Jeremias; Kolmhuber, Stefanie; Krauss, Sabine H.; Odierna, Beatrice; Rémi, Constanze; Schildmann, Jan; et al. (Palliative Medicine Reports, 2024)
Background: The option of intentional sedation to relieve intolerable suffering from treatment-refractory symptoms may elicit a feeling of safety for patients and informal caregivers as a last resort if the situation becomes unbearable. Many health care professionals feel uncomfortable and insecure in conducting intentional sedation due to specific challenges. We developed a complex intervention to support best practice use of sedative drugs in specialist palliative care in Germany based on previously published recommendations. This article aims at reporting the development of the intervention. Methods: The development of the intervention was based on theory and existing evidence with active stakeholder participation and patient and public involvement, following the updated Medical Research Council (MRC) Framework on complex interventions. A “Theory of Change,” drawing on expert-approved best practice recommendations and applying user-centered methods, fostered the development. The process encompassed study preparation, development of the elements of the intervention, and designing the multimodal intervention. For reporting, we adhere to the Guidance for Reporting Intervention Development framework. Results: The intervention is aimed at health care professionals working in specialist palliative care (inpatient and homecare settings) and consists of several components: (1) a screening tool, (2) the individual elements of the intervention, and (3) educational material for health care professionals to support them using the intervention. Additional information material was developed for patients and informal caregivers. Despite the benefits of stakeholder involvement, we faced some barriers due to limited health care staff and time resources and reservations regarding research in general. Discussion: A pilot study is planned for testing the overall feasibility of the intervention and exploring possible benefits for health care professionals to inform a subsequent fully powered implementation study. To deal with the challenges, we stayed in contact with the health care teams, maintained transparency, and provided opportunities for active participation.
CRIS-Team Scopus Importer:2025-02-04
Keywords: complex intervention; GUIDED; intervention development; palliative care; sedative drugs; theory of change

Documentation of Sedation in Palliative Care: A Scoping Review of Requirements, Recommendations, and Templates - Kauzner, Saskia; Heckel, Maria; Ostgathe, Christoph; Schneider, Manuela; Bausewein, Claudia; Schildmann, Eva; Kremling, Alexander; Ziegler, Kerstin; Klein, Carsten (Journal of Palliative Medicine, 2023)
Objective: To identify and describe requirements, recommendations, and templates for the documentation of sedation in adult palliative care.Introduction: International literature shows inconsistency in clinical practice regarding sedation in palliative care accompanied by legal, ethical, and medical uncertainties. Documentation in general serves as proof for previous treatments. In the context of intentional sedation to relieve suffering at the end of life, documentation provides a clear demarcation against practices of euthanasia.Inclusion Criteria: Articles with full-text version published in English or German since 2000, covering documentation requirements, recommendations, monitoring parameters or templates for sedation in adult palliative care were included.Methods: Scoping review following the JBI methodology. Search in online databases, websites of professional associations in palliative care, reference lists of relevant publications, the archive of the German "Journal of Palliative Medicine" and databases for unpublished literature were used. Search terms included "palliative care,' "sedation," and "documentation." The search was conducted from January 2022 to April 2022 with an initial hand search in November 2021. Data were screened and charted by one reviewer after conducting a pilot test of the criteria.Results: From the initial 390 articles (database search), 22 articles were included. In addition, 15 articles were integrated from the hand search. The results can be clustered in two sets of items, regarding either the documentation before or during sedation. The documentation requirements referred both to inpatient and homecare settings but in many cases, a clear assignment was missing.Conclusions: The guidelines analyzed in this study rarely cover setting-specific differences in documentation and often treat documentation as minor topic. Further research is needed addressing legal and ethical concerns of health care teams and, therefore, help to improve treatment of patients suffering from otherwise intractable burden at the end of life.
CRIS-Team WoS Importer:2023-05-26

Expert-approved best practice recommendations on the use of sedative drugs and intentional sedation in specialist palliative care (SedPall) - Ostgathe, Christoph; Bausewein, Claudia; Schildmann, Eva; Bazata, Jeremias; Handtke, Violet; Heckel, Maria; Klein, Carsten; Kremling, Alexander; Kurkowski, Sandra; Meesters, Sophie; Seifert, Andreas; Torres Cavazos, Jorge; et al. (BMC Palliative Care, 2023)
Background: The use of sedative drugs and intentional sedation in end-of-life care is associated with clinical, ethical and legal challenges. In view of these and of the issue’s great importance to patients undergoing intolerable suffering, we conducted a project titled SedPall (“From anxiolysis to deep continuous sedation – Development of recommendations for sedation in palliative care“) with the purpose of developing best practice recommendations on the use of sedative drugs and intentional sedation in specialist palliative care and obtaining feedback and approval from experts in this area. Design: Our stepwise approach entailed drafting the recommendations, obtaining expert feedback, conducting a single-round Delphi study, and convening a consensus conference. As an interdisciplinary group, we created a set of best practice recommendations based on previously published guidance and empirical and normative analysis, and drawing on feedback from experts, including patient representatives and of public involvement participants. We set the required agreement rate for approval at the single-round Delphi and the consensus conference at ≥80%. Results: Ten experts commented on the recommendations’ first draft. The Delphi panel comprised 50 experts and patient and public involvement participants, while 46 participants attended the consensus conference. In total, the participants in these stages of the process approved 66 recommendations, covering the topics “indications”, “intent/purpose [of sedation]”, “decision-making”, “information and consent”, “medication and type of sedation”, “monitoring”, “management of fluids and nutrition”, “continuing other measures”, “support for relatives”, and “team support”. The recommendations include suggestions on terminology and comments on legal issues. Conclusion: Further research will be required for evaluating the feasibility of the recommendations’ implementation and their effectiveness. The recommendations and the suggested terminology may serve as a resource for healthcare professionals in Germany on the use of sedative drugs and intentional sedation in specialist palliative care and may contribute to discussion on the topic at an international level. Trial Registration: DRKS00015047 (German Clinical Trials Register)
CRIS-Team Scopus Importer:2023-09-15
Keywords: Community-based participatory research; Empirical research; Hypnotics and sedatives; Palliative care; Practice guidelines; Terminal care

Intentional Sedation as a Means to Ease Suffering: A Systematically Constructed Terminology for Sedation in Palliative Care - Kremling, Alexander; Bausewein, Claudia; Klein, Carsten; Schildmann, Eva; Ostgathe, Christoph; Ziegler, Kerstin; Schildmann, Jan (Journal of Palliative Medicine, 2022)
Background: Terminology concerning sedation in palliative care is heterogeneous, vague, and difficult to apply with negative impact on the reliability of quantitative data, practice, and ethical discourse.Design: To clarify the concept, we systematically developed definitions of core terms in an interdisciplinary research group comprising palliative care, ethics, law, and philosophy, integrating feedback from external experts.Results: We define terms stepwise, separating matters of terminology (What is the practice?) from matters of good practice (How to use it?). We start with an operational definition of "reduced level of consciousness" (score < 0 on the Richmond Agitation-Sedation Scale modified for palliative care inpatients (RASS-PAL), followed by defining "sedating," "sedation," and "intentional sedation" as the result or process of sedating a patient as a means of achieving a previously defined treatment goal and the terms "light," "deep," "temporary," and "sedation until death."Conclusion: The terminology facilitates the precise phrasing of aims, indications, and rules for good practice. Empirical research on acceptance and feasibility is needed.
CRIS-Team WoS Importer:2022-03-04

More Barriers than Bridges - Research in Times of the GDPR - Kurkowski, Sandra; Ziegler, Kerstin; Jäger, Christian; Torres Cavazos, Jorge; Heckel, Maria; Klein, Carsten; Ostgathe, Christoph (Zeitschrift für Palliativmedizin, 2022)
CRIS-Team WoS Importer:2022-03-18

Terminological Confusion About Sedation in Palliative Care: Results of an International Online Vignette Survey - Kremling, Alexander; Bausewein, Claudia; Klein, Carsten; Nadolny, Stephan; Ostgathe, Christoph; Schildmann, Eva; Ziegler, Kerstin; Schildmann, Jan (Journal of palliative medicine, 2024)
Background: Terminological problems concerning sedation in palliative care and consequences for research and clinical decision making have been reported frequently. Objectives: To gather data on the application of definitions of sedation practices in palliative care to clinical cases and to analyze implications for high-quality definitions. Design: We conducted an online survey with a convenience sample of international experts involved in the development of guidelines on sedation in palliative care and members of the European Association for Palliative Care (EAPC). Participants were asked to apply four published definitions to four case vignettes. Data were analyzed using descriptive statistics. Results: A total of 32 experts and 271 EAPC members completed the survey. The definitions were applied correctly in n = 2200/4848 cases (45.4%). The mean number of correct applications of the definitions (4 points max.) was 2.2 ± 1.14 for the definition of the SedPall study group, 1.8 ± 1.03 for the EAPC definition, 1.7 ± 0.98 for the definition of the Norwegian Medical Association, and 1.6 ± 1.01 for the definition of the Japanese Society of Palliative Medicine. The rate of correct applications for the 16 vignette-definition pairs varied between 70/303 (23.1%) and 227/303 (74.9%). The content of definitions and vignettes together with free-text comments explains participants' decisions and misunderstandings. Conclusions: Definitions of sedation in palliative care are frequently incorrectly applied to clinical case scenarios under simplified conditions. This suggests that clinical communication and research might be negatively influenced by misunderstandings and inconsistent labeling or reporting of data. Clinical Trial Registration Number: DRKS00015047.
CRIS-Team Scopus Importer:2024-04-19
Keywords: cross-sectional survey; deep sedation; palliative care; palliative sedation; terminology; vignette study

Use of sedative drugs in specialist palliative care (iSedPall): a multi-modal intervention pilot study protocol - Ostgathe, Christoph; Bausewein, Claudia; Schildmann, Eva; Bazata, Jeremias; Heckel, Maria; Kauzner, Saskia; Klein, Carsten; Krauss, Sabine H.; Kremling, Alexander; Schneider, Manuela; Seifert, Andreas; Ziegler, Kerstin; et al. (Pilot and Feasibility Studies, 2025)
Background: The use of sedative drugs in specialist palliative care is common but presents challenges due to specific medical, ethical, and legal considerations. There is little to no assistance for administering adequate sedative drug doses, ensuring accurate documentation before and during sedation, or managing ethically and legally challenging situations. In 2021, the SedPall study group published recommendations on the use of sedative drugs in palliative care. The German Association for Palliative Medicine endorsed the dissemination of the recommendations nationwide. However, disseminating recommendations alone does not necessarily lead to changes in clinical practice. In the project “Development and piloting of a multi-modal intervention for the use of sedative drugs in specialist palliative care (iSedPall)”, we will develop a multi-modal intervention that implements these national recommendations into practical tools for healthcare professionals in specialist inpatient and home care settings. In the pilot study described below, we aim to test the feasibility of the multi-modal intervention, its appropriateness, and acceptability as primary feasibility outcomes of the multi-modal intervention. Additionally, we aim to assess the feasibility of measuring healthcare professionals´ confidence in using sedative drugs as an outcome indicator for a possible subsequent study. Methods and analysis: We will use a mixed-methods approach to develop and pilot a multi-modal intervention. The primary feasibility outcomes and formative evaluation of the implementation process will be explored using quantitative (retrospective cohort study, survey) and qualitative elements (focus groups, interviews). Additionally, we will pilot the measurement of healthcare professionals´ confidence in using sedative drugs as an outcome indicator through a pre-post survey. Four specialist palliative care services will pilot the complex intervention for nine months. Due to the complexity of the intervention, we will follow the principles of the MRC framework for complex interventions and will apply a Theory of Change approach. The intervention will include different elements to be used throughout the patients’ treatment in inpatient and home specialist palliative care considering medical, ethical, and legal aspects for the use of sedative drugs and intentional sedation. The evaluation of the overall feasibility and the decision about proceeding to an implementation study will be based on the integration of quantitative and qualitative data, according to our mixed-methods approach. Discussion: This project is the first attempt to translate national recommendations on best practices for sedative drug use into a multi-modal intervention and tests its feasibility. The study group identified potential risks and challenges related to the intervention´s feasibility, acceptability, and appropriateness in advance. To mitigate these risks, the study protocol is based on a theoretical framework, developed through a Theory of Change approach. Participatory elements and the involvement of different stakeholders are expected to enhance user acceptance and feasibility, potentially improving the development of supporting materials for sedative drug use in specialist palliative care while considering the interests of non-professionals. Trial registration: Registered in the German Clinical Trials Register, DRKS-ID: DRKS00027241; Registered: 10/12/2021; https://www.drks.de/drks_web/setLocale_EN.do.
CRIS-Team Scopus Importer:2025-05-30
Keywords: Multi-modal intervention; Palliative care; Sedative drugs; Study protocol